(untitled) (Journal of Preventive and Social Medicine, 2020)
Background: Unwanted pregnancy is common in slum dwelling couples as they are less aware about postpartum contraceptive. Unmet need of postpartum contraceptive is also evident in slums. Objective: This study aims to assess the unmet need of post-partum contraceptives used in urban slums. Materials and Methods: This study was a cross-sectional study on fecund women in postpartum period (0 months to 24 month). A total of 162 postpartum women were face to face interviewed with a pretested semi structured questioner by using software SPSS- 20. Place and period: The study was conducted in slum area of Jurain and Moghbazar in Dhaka city, during the period of January 2016 to December 2016. Results: About 51.2% (83) of the respondents were in the age group of 22-26 years. Almost 53.1% (86) of the respondents were illiterate. 57.4% (93) of the respondents were housewife. 61.1% of the respondents gave history of monthly family income of 4200-5700 taka. Total unmet need of postpartum contraceptive period, among 162 respondents were 58% about 94 and met need 42% (68). Intention for contraceptives used, were 86% (81) among 94 respondents. Factors related with unmet need – All most 45.7% of the respondents were not used any contraceptives due to not approved by their husband among 94 respondents. Decision regarding family planning has given by husband 51.85% (84). There were significant association with education and unmet need of contraceptives use (p<0.05). Monthly family income was significant association with unmet need of contraceptives use (p<0.05). Conclusions: Unmet need for family planning has been a major concern for international population since several decades. Present study indicated a high unmet need for postpartum contraception in the selected area of urban slums in Dhaka city, with a scope to decrease constraints and address user perspective to meet the contraception needs.Change in the attitude of the husband, family and society to accept equity and equality of women and men can positively lead women’s unmet need of family planning during postpartum periods. JOPSOM 2019; 38(2): 46-52